Determinants of cerebral collateral circulation in acute ischemic stroke due to large vessel occlusion - Sperti, Martina; Arba, Francesco; Acerbi, Amedeo; Busto, Giorgio; Fainardi, Enrico; Sarti, Cristina (Frontiers in Neurology, 2023)
Introduction Cerebral collateral circulation has a central role in ischemic stroke pathophysiology, and it is considered to correlate with infarct size, the success of reperfusion therapies, and clinical outcomes. Our aim was to study the factors influencing the development of collaterals in patients with acute ischemic stroke eligible for endovascular treatment. Materials and methods We enrolled patients with acute ischemic stroke and large vessel occlusion of anterior circulation potentially eligible for endovascular treatment. Included patients performed multiphase CT angiography to assess collaterals that were graded by the Menon Grading Score. We investigated the associations between clinical factors and collaterals and tested independent associations with logistic (good vs. poor collaterals) and ordinal (collateral grade grouped, Menon 0–2, 3, 4–5) regression analysis adjusting for age, sex, stroke severity, and onset to CT time (OCTT). Results We included 520 patients, the mean age was 75 (±13.6) years, 215 (41%) were men, and the median (IQR) NIHSS was 17 (11–22). Good collaterals were present in 323 (62%) patients and were associated with lower NIHSS (median 16 vs. 18; p < 0.001) and left hemisphere involvement (60% vs. 45%; p < 0.001), whereas previous stroke/TIA was more frequent in patients with poor collaterals (17 vs. 26%; p = 0.014). These results were confirmed in both logistic and ordinal regression analyses where good collaterals were associated with lower NIHSS (OR = 0.94; 95% CI = 0.91–0.96; cOR = 0.95; 95% CI = 0.92–0.97, respectively) and left hemisphere stroke (OR = 2.24; 95% CI = 1.52–3.28; cOR = 2.11; 95% CI = 1.46–3.05, respectively), while previous stroke/TIA was associated with poor collaterals (OR = 0.57; 95% CI = 0.36–0.90; cOR = 0.61; 95% CI = 0.40–0.94, respectively). Vascular risk factors, demographics, and pre-stroke treatments did not influence the collateral score. Discussion The results of our study suggest that risk factors and demographics do not influence the development of collateral circles, except for a negative relation with previous ischemic events. We confirm an already reported observation of a possible protective effect of collaterals on tissue damage assuming NIHSS as its surrogate. The association between left hemispheric stroke and better collaterals deserves to be further explored. Further efforts are needed to identify the factors that favor the development of collaterals.